STRATEGY OF PROMOTION IN HEARING HEALTH: FLIER WITH 9 STEPS FOR THE CARE OF HEARING! (Fiep Bulletin - online, 2016)
Pedagogical techniques have been used as a mean strategic facilitator of knowledge transmission. The objective was to present the proposal of 9 steps for the care of hearing. For the development of the flier, the PET team Health/Hearing Health Care Networks gathered in five meetings by setting up: the used resource (flier) and contents of the flier. Elaborated a draft of the visual structure of the flier. After approval and testing, the flier went to press. 9 steps have been defined on the hearing health care: Step 1: Excessive noise can cause irreversible hearing loss. Avoid! Step 2: Do not insert sharp objects like pencils, clips, toothpicks, among others in the ear. Step 3: Wrap the tip of his finger in the towel to sanitize the outer part of the ear. Avoid cotton swab! Step 4: Use drugs only with prescription from a health professional. Step 5: Use the headset properly: lower volume than that of normal speech, preferring phones clamshell format. Step 6: Our ears also need to rest. Avoid noise and headphones while sleeping. Step 7: Caring for the hearing health begins before birth. Pregnant women make prenatal care. Step 8: Vaccinate children against measles, mumps and meningitis, as these diseases can cause hearing damage. Step 9: Rest your hearing for a few minutes every day, especially if you are exposed to excessive noise. The flier includes information on hearing health covering different age groups, being an educational method in health easily understood and distribution.
Keywords: Hearing Health; Health Promotion; Hearing.